Identification of Phenotypic Variation of Kampung Chicken in Kalemago Village, East Lore District, Poso Regency - Azmizam, Nurul; Teguh, Muhammad (Fakultas Peternakan, Universitas Padjadjaran, 2025)
Kampung chickens are one of the most widely raised types of poultry in Indonesia and have high genotype and phenotype variations. This study aimed to identify phenotypic variations of Kampung chickens in Kalemago Village, East Lore District, Poso Regency, Central Sulawesi. This study was conducted to understand the variations in quantitative and qualitative traits in Kampung chickens in the Poso Regency. Quantitative traits observed include body weight, back length, chest circumference, length of upper thigh bone, lower thigh bone, and shank, while qualitative traits include feather color, comb type, beak color, and shank color. Measurements were conducted on male and female Kampung chicken populations. The results of the study showed significant diversity in quantitative and qualitative traits of Kampung chickens in Kalemago Village, which can be used as a basis for breeding programs to increase Kampung chicken productivity.